Evidence on why firms use different disclosure outlets: Purchased analyst research, investor presentations and Open Briefings. Issue 3 (5th September 2016) - Feigin, Alexey; Ferguson, Andrew; Grosse, Matthew; Scott, Tom
Abstract : Purpose: The purpose of this study is to consider why firms use different disclosure outlets. The authors argue that the firm's choice of disclosure outlet can be explained by voluntary disclosure theories and investigate whether the market response around different disclosure outlets varies. Design/methodology/approach: The authors investigate differences in the characteristics of firms purchasing analyst research, holding investor presentations or Open Briefings and compare market reactions around each disclosure event. Findings: The authors find that firm incentives to reduce information acquisition costs or mitigate disclosure risk affect firm disclosure outlet choice, and mixed evidence in support of talent signalling motivations. There is a lower absolute abnormal return around Open Briefings and a higher signed abnormal return around purchased analyst research. Research limitations/implications: The research is exploratory in nature and only considers a small subset of disclosure outlets. There may be differences in information content across disclosure outlets. Originality/value: They show disclosure outlets are not homogenous and provide empirical evidence voluntary disclosure theories help explain differences between firms' use of disclosure outlets. Considering the growing number of disclosure outlets available, disclosure outlet choice is likely to be an increasingly important topic in accounting research.